Modus Operandi Transaksi Narkotika oleh Anak Melalui Media Digital dan Implikasi Hukumnya - M. Julianto Al Hakim; Diah Gustiniati Maulani; Dona Raisa Monica (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
The illicit circulation of narcotics in Indonesia has undergone a fundamental evolution into cyber-enabled crime, where drug syndicates systematically exploit children as technical operators through digital media to sever the main network chain and evade legal detection. This study aims to analyze the anatomy of the modus operandi of narcotics transactions involving children in the digital realm and examine its legal implications for the process of proof and criminal liability. Utilizing an empirical juridical research method with a sociological approach conducted in the jurisdiction of the Metro Police Resort, Lampung, this research identifies a shift in modus operandi towards the "Map System" or Dead Drop Method. In this modus, the child's role is divided into three sophisticated technical stages: pre-transaction via encrypted communication, field execution (mapping & dropping) using precise GPS coordinates, and post-transaction involving digital cleaning, which creates a phenomenon of crime "gamification" where children perceive the criminal act akin to an online game mission. The legal implications of this phenomenon present serious challenges regarding the validity of electronic evidence, which is volatile due to a weak chain of custody, as well as the reconstruction of the child's mens rea, which points towards premeditated intent (dolus premeditatus) driven by high digital literacy rather than mere negligence. These conditions complicate the application of pure diversion as mandated by law; thus, this study recommends a hybrid punishment approach where law enforcement proceeds to break impunity, but sanctions focus on specific rehabilitation in the Special Guidance Institution for Children (LPKA) to reorient the children's digital skills positively.